Proteomic analysis of Red Sea Conus taeniatus venom reveals potential biological applications - Maged M. A. Fouda; Mohammed Abdel-Wahab; Amal Mohammadien; Mousa O. Germoush; Moustafa Sarhan (Journal of Venomous Animals and Toxins including Tropical Diseases, 2021)
Abstract Background: Diverse and unique bioactive neurotoxins known as conopeptides or conotoxins are produced by venomous marine cone snails. Currently, these small and stable molecules are of great importance as research tools and platforms for discovering new drugs and therapeutics. Therefore, the characterization of Conus venom is of great significance, especially for poorly studied species. Methods: In this study, we used bioanalytical techniques to determine the venom profile and emphasize the functional composition of conopeptides in Conus taeniatus, a neglected worm-hunting cone snail. Results: The proteomic analysis revealed that 84.0% of the venom proteins were between 500 and 4,000 Da, and 16.0% were > 4,000 Da. In C. taeniatus venom, 234 peptide fragments were identified and classified as conotoxin precursors or non-conotoxin proteins. In this process, 153 conotoxin precursors were identified and matched to 23 conotoxin precursors and hormone superfamilies. Notably, the four conotoxin superfamilies T (22.87%), O1 (17.65%), M (13.1%) and O2 (9.8%) were the most abundant peptides in C. taeniatus venom, accounting for 63.40% of the total conotoxin diversity. On the other hand, 48 non-conotoxin proteins were identified in the venom of C. taeniatus. Moreover, several possibly biologically active peptide matches were identified, and putative applications of the peptides were assigned. Conclusion: Our study showed that the composition of the C. taeniatus-derived proteome is comparable to that of other Conus species and contains an effective mix of toxins, ionic channel inhibitors and antimicrobials. Additionally, it provides a guidepost for identifying novel conopeptides from the venom of C. taeniatus and discovering conopeptides of potential pharmaceutical importance.